LEARNING ASSESSMENT AND IMPLICATIONS FOR EDUCATION INSTITUTIONS IN MALAYSIA (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThis concept paper aims to identify the appropriate assessment practices in theeducation system in Malaysia. It is particularly significant because the assessment isthe heart of the studentsâ learning experience which reflect the real curriculum. A lotof time and attention spent by the students on the assessment.Theseaffects behaviourand their learning styles. The study found that there were still problems in thepractice of assessment in teacher education in Malaysia,more likely the writtenexaminationthat have shaped the minds of students to be rigid and static, gearedtoexam oriented. It is necessary to find a solutionto this problem as to produce a betterstudents in future generation. The assessment practice should be able to meet thegovernments intention to produce a holistic and quality of human capital in order tosuccessfully face the challenges of globalization. At the school level in Malaysia, theimplementation of the National Education Assessment System (NEAS) hasemphasized the approach of assessment for learning and assessment of learning. Theproblem arises because bothapproaches in assessment are teacher-centred,whereteachers are the appraiser. It should be a learning assessment (assessment aslearning) and character assessment because this approach focuses on the role ofstudents as the appraiser. Hence, the need for assessment practices that emphasizefour approaches to learning (for, as, of and character) known as learningassessments. It aims to help improve the quality of students from a variety of aspects,including learning and their own potential. Learning assessment can haveimplications for education institutions and the role of teachers as educators toencourage lifelong learning and generate quality human capital.Key words: assessment for learning, assessment as learning, assessment of learning,learning assessment, implications